Analiza instrumentarium wspierającego proces restrukturyzacji finansowej przedsiębiorstw w USA - Rochoń, Małgorzata (The Analysis of a Tool Kit for Supporting the Financial Restructuring of Enterprises in the United States of America, 2007)
In today's complex economic and social environment in which market forces are changing quickly and radically many companies face deterioration of economic and financial standing. This eventually threatens the further existence of a company and its capacity to meet liabilities towards creditors and may inevitably lead to a bankruptcy. An alternative to bankruptcy is a financial restructuring. In polish realities, financial restructuring finds application first of all for reduction of debt of enterprise and it proceeds in practice at use very narrow and limited instruments spectrum and operations. It indicate practice of application of financial restructuring in United States, that this process brings enterprises on market measurable benefit in the form not only survive, but first of all, recoveries of competitiveness. There is result, that American enterprises use, from the point of view of greatest availability instruments at the nature development and simultaneously using operations at the nature perspective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 455-460